Numerical study of the effect of channel geometry on the performance of Magnetohydrodynamic micro pump - Mushtaq Ismael Hasan; Abdul Jabbar F. Ali; Rhan S. Tufah (Engineering Science and Technology, an International Journal, 2017)
Magnetohydrodynamic micropumps received more attention due to its applications in pumping of biological and chemical specimens, such as blood, DNA, and saline buffers. In this paper the MHD flow in different cross section microchannels has been numerically investigated with different electromagnetic boundary conditions. Square, rectangular, circular and trapezoidal cross section microchannels have been used to explore the effect of channel geometry on the MHD micropump operation. The study covers a selected range of applied electric currents and magnetic flux to show their effects on MHD flow. Thermal characteristics of MHD flow have been also studied by calculation the temperature distribution through MHD micropump region. The results obtained show a considerable effect of channel geometry, the applied electric and magnetic fields on the velocity and flow rate. The circular cross section micropump gave higher velocity and flow rate compared with other cross sections, and there is a slight increase in temperature due to small effect of Joule heating.